Analisis Kualitas Pelayanan (Jasa), Kepuasan Mahasiswa, Dan Loyalitas Mahasiswa (Studi Kasus Pada STIE Bisnis Dan Perbankan 2019) - Zulhaq K Siahaan; Wening N (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
This study aims to analyze service quality in higher eduation, student satisfaction, and student loyalty at STIE Bisnis dan Perbankan Yogyakarta. This reasearch is a quantitavive based descriptive research.Using a sample of 188 students showed that there is a good enough service quality perceived by students, student satisfaction, and student loyalty.The limitation of this reasearch is that this study is limited on STIEBBANK students and can not be generalized on all higher education students. The suggestions are given as the managerial implications of this internship study. Broadly, STIEBBANK needs to maintain and to increase quality service in higher education, student satisfaction, and student loyalty.